Analisis Manajemen Sarana dan Prasarana Pada Pembelajaran - Ifroh Hayana; Nini Aryani; Paijan Rambe (P3M STKIP 'Aisyiyah Riau, 2021)
The problem of this research is the lack of planning prepared by the foundation and the principal in improving the facilities and infrastructure in learning, so that it seems that the school is less advanced and developing. The purpose of this research is to describe the management of facilities and infrastructure for early childhood learning in TK Fahria Hayana Siak Hulu, Kampar Regency. This type of research uses qualitative research methods. The time of the study was carried out from April to August 2021. The place of research was at Fahria Hayana Kindergarten which is located on Jl. Pandau Permai (Behind the White Sand Gas Station). The research subjects consisted of 1 administrator of the foundation, 1 principal and 1 teacher. The results of this study are that the management of infrastructure in TK Fahria Hayana Siak Hulu is classified as good. The conclusion of the study is that the management of infrastructure facilities in early childhood learning at Fahria Hayana Siak Hulu Kindergarten has been managed properly and through the stages of planning, organizing, implementing and supervising the facilities and infrastructure